Proposed Amendment on the Reform of the IMF Executive Board and Fourteenth General Review of Quotas : Status of Acceptances and Consents. (Policy Papers; Policy Paper ;, 2012)
This status report reviews progress toward implementation of the 2010 Governance and Quota Reforms. It updates the status of consents to the proposed quota increases under the 14th General Review of Quotas and of acceptances of the Proposed Seventh Amendment on the Reform of the Executive Board ('Board Reform Amendment' or 'Seventh Amendment') as set out in the Board of Governors Resolution No. 66-2. For the proposed quota increases under the 14th General Review of Quotas to become effective, members having not less than 70 percent of the total of quotas on November 5, 2010 must consent to the increases in their quotas and the proposed Board Reform Amendment must have entered into force. The proposed Board Reform Amendment enters into force once the Fund certifies that three-fifths of the members (i.e., currently 113 members) representing 85 percent of the total voting power have accepted the proposed amendment.